Proverbs - Kirkpatrick, Betty (Learners Pub, 2003)
This book contains a selection of common proverbs with explanations of their origins and alternative forms where appropriate, over 1000 example sentences, 13 passages showing the proverbd in context and 10 sets of questions, with answers, for seft-testing